Visual assessment of dynamic knee joint alignment in patients with patellofemoral pain: an agreement study - Hansen, Rudi; Lundgaard-Nielsen, Mathilde; Henriksen, Marius (PeerJ, 2021)
Background Assessment of knee kinematics plays an important role in the clinical examination of patients with patellofemoral pain (PFP). There is evidence that visual assessments are reliable in healthy subjects, but there is a lack of evidence in injured populations. The purpose of this study was to examine the intra- and interrater agreement in the visual assessment of dynamic knee joint alignment in patients with PFP. Methods The study was a cross-sectional agreement study. Sixty participants (42 females) were included. We assessed the intra- and interrater agreement of two functional tests: The single leg squat (SLS) and the forward lunge (FL). One investigator scored the movement according to preset criteria while video recording the movement for retest. Moreover, the performance was scored by another investigator using the video recording. Agreement was assessed using weighted kappa statistics. Results The intrarater agreement ranged from moderate to good (Kappa 0.58 (FL) to 0.70 (SLS)) whereas the interrater agreement ranged from fair to moderate (Kappa 0.22 (SLS) to 0.50 (FL)). Conclusion The agreement within raters was better than between raters, which suggests that assessments should preferably be performed by the same tester in research and in a clinical setting, e.g., to evaluate any treatment effect. We promote FL as a reliable clinical tool for evaluating dynamic knee alignment, since it shows equally good intra- and interrater agreement, and it is an inexpensive and easy method to use.
Keywords: Agreement; Knee Alignment; Patellofemoral Pain; PFP; Visual Assessment; Reliability; Knee Kinematics